Management of local recurrences and regional failure in early stage non-small cell lung cancer after stereotactic body radiation therapy - Kumar, Sameera S. (Transl Lung Cancer Res, 2019)
Stereotactic body radiation therapy (SBRT) is a very effective way to treat early stage non-small cell lung cancer (NSCLC) and small oligometastatic lung lesions with consistently high rates of local control, but both local and regional/distant recurrences still occur. The management of recurrences remains unsettled and may entail repeat SBRT, conventionally fractionated external beam RT (EF-EBRT), chemotherapy or surgery. Most patients with local recurrences [within the initial planning target volume (PTV)] can be salvaged successfully with good cancer specific survival. Nonetheless, proximity of the initial SBRT delivery to organs at risk (ribs, blood vessels, airways) may make retreatment more difficult. With attention to detail and careful patient selection, both surgery and reirradiation can be performed safely and effectively. Strategies for management of regional (nodal) recurrences may require conventional therapies tailored to the patterns of failure. The role of immunotherapy in salvage has not been elucidated as yet. We review here data on the available literature concerning salvage of SBRT lung patients.